Enhancing lignin depolymerization via a dithionite-assisted organosolv fractionation of birch sawdust. Issue 9 (28th April 2021) - Brienza, Filippo; Van Aelst, Korneel; Thielemans, Karel; Sels, Bert F.; Debecker, Damien P.; Cybulska, Iwona
Abstract : A dithionite-assisted organosolv fractionation process is presented, for the treatment of raw lignocellulose and the concomitant production of cellulosic pulp and the reductive conversion of lignin into phenolic monomers and short oligomers. Abstract : Sodium dithionite is utilized as a reducing agent in the organosolv fractionation of lignocellulose to concomitantly produce cellulosic pulp and promote the reductive conversion of lignin into phenolic monomers. Reactions with model compounds highlight the role of sodium dithionite with respect to the reductive cleavage of β-O-4 bonds in lignin and the consequent formation of phenolic monomers.